2021
DOI: 10.1021/acs.chemrev.0c00779
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Alternative Strategies for Enhanced Nanoparticle Delivery to Solid Tumors

Abstract: Nanomaterial (NM) delivery to solid tumors has been the focus of intense research for over a decade. Classically, scientists have tried to improve NM delivery by employing passive or active targeting strategies, making use of the so-called enhanced permeability and retention (EPR) effect. This phenomenon is made possible due to the leaky tumor vasculature through which NMs can leave the bloodstream, traverse through the gaps in the endothelial lining of the vessels, and enter the tumor. Recent studies have sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
237
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 302 publications
(240 citation statements)
references
References 523 publications
1
237
0
2
Order By: Relevance
“…Recently, numerous studies have reported that biodegradable polymeric nanocarriers possess a superior stealth function for the detection of the reticuloendothelial system in the human body and exhibit an enhanced permeability and retention effect [ 56 , 57 , 58 , 59 , 60 , 61 ]. In particular, these polymeric nanoparticles are capable of having several beneficial properties, such as biomimetics, stimuli-sensitivity, easy modification, and exquisite target specificity compared to carriers composed of other materials.…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…Recently, numerous studies have reported that biodegradable polymeric nanocarriers possess a superior stealth function for the detection of the reticuloendothelial system in the human body and exhibit an enhanced permeability and retention effect [ 56 , 57 , 58 , 59 , 60 , 61 ]. In particular, these polymeric nanoparticles are capable of having several beneficial properties, such as biomimetics, stimuli-sensitivity, easy modification, and exquisite target specificity compared to carriers composed of other materials.…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…Among the nanocarriers that are being developed for the diagnosis and treatment of cancer are inorganic nanoparticles, which may consist of iron oxide, silica, gold, and graphene, among other compounds [ 46 ]. There is greater difficulty in translating these types of nanomaterials (NMs) to clinical application, due to their lower biocompatibility and the lack of understanding of possible complications caused by their deposition in different organs, such as greater stability, less hydrophobicity, and non-microbial storage [ 47 , 48 ].…”
Section: Classification Of Nanocarriersmentioning
confidence: 99%
“…Nowadays, drug delivery has become one of the most controversial issues, which is also the top concern of all anticancer therapies, with the rapid development of nanomedicines [1][2][3][4][5] . The major obstacle in achieving better delivery e ciency is the abnormally high tumor interstitial pressure (TIP) [6][7][8][9] .…”
Section: Introductionmentioning
confidence: 99%
“…However, the interstitial pressure in the tumor is as high as 30~130 mmHg due to the retention of interstitial uid caused by de cient lymph-vessel and lymphatic re ux, as well as dense extracellular matrix (ECM) [13][14][15] . The much smaller net outward pressure or even net inward pressure seriously limits the normal ow from vessels into the tumor 3 , which leads to unsatisfactory delivery e ciency of therapeutic agents. Among the mounting works on drug delivery, most efforts focus on reducing tumor interstitial solid pressure (TISP) caused by dense ECM, proteins, and broblasts via enzymolysis, which left the mass deposition of interstitial uid unsolved [16][17][18] .…”
Section: Introductionmentioning
confidence: 99%